Hepatocellular injury in children treated for rifampicin-resistant tuberculosis: incidence, aetiology and outcome - Duvenhage, Joanie (Stellenbosch : Stellenbosch University, 2022)
Thesis (MMed) -- Stellenbosch University, 2022.